Seed Quality Analysis of Field Pea (Pisum Sativum L.) from Formal and Informal Sources in Enarj Enawuga and Yilmana Densa Districts, West Amhara Region, Ethiopia - Yenus Ali; Firew Mekibib; Zewdie Bishaw (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2021)
The production and productivity of field pea crop in Amhara region depends mainly on the un availability of quality seed supply system for a number of improved varieties. Therefore, this study was conducted to assess the quality and seed management practices of field pea seeds from the informal and formal seed systems in Enarj Enawuga and Yilmana Densa Districts during 2016/17 cropping season. Seed samples of two field pea varieties were collected from both formal and informal sectors and tested for quality in Complete Randomized Design (CRD) with four replications. The quality of seed samples had significant difference for physical purity, germination and vigor indices among seed samples. Except for other crop seeds, all the seed samples from informal seed sector maintained the physical /analytical/ purity of seed quality components (above the standards). Most of the seed samples except four samples (seed samples collected from farmer two and twelve of Enarj Enawuga districts who grow Tegegnech variety (F2 and F12),  farmer 18 and 22 of Yilmana Densa districts who grow Tegegnech variety (F18 and F22) had registered germination capacity above the standards (75%). The speed of germination was better to predict field emergence of the seed lot than the standard germination. Seedborne fungi such as Ascochyta pinodes, Ascochyta pisi, Fusarium sp, Phoma sp, Septoria pisi, Colletotrichum sp were found associated with the field pea seed. Among those fungi Ascochyta pinodes was the dominant. Most farmer seed management practices enable to maintain and improve their field pea seed quality in both districts.  Extension should play a crucial role in training farmers in on-farm quality seeds of the field pea crop production and is therefore a prerequisite for the improvement of the informal seed system in both districts.